Study on the Optimization of Management of Parking Retributions on the Roadside of Public Roads at the City of Ternate Transportation Services - Ahmad Yani Abdurrahman; Aswir Hadi; Ida Bagus Benny Surya Adi Pramana (Budapest International Research and Critics University, 2022)
This study aims to identify problems related to optimizing the management of parking fees on the edge of public roads carried out by the Department of Transportation of the City of Ternate, to map and describe and examine phenomena related to objects. The research method used in this research is descriptive exploratory with the characteristics of focusing on problem solving, then data is collected, compiled, explained and analyzed. The unit of analysis in this study is the stakeholders related to the management of parking fees and interviews with authorized officials. The results of this study prove that the Ternate City Transportation Service has not optimally implemented parking retribution management on the edge of public roads so that the target for local revenue originating from parking fees does not reach the target. Even the realization of revenue from parking fees on the side of public roads does not show an increasing trend every year but on the contrary is very volatile, this study also finds the cause of the low acceptance of parking fees on public roads because there are still many parking points which are potential revenues that have not been worked out optimally, limited resources and not supported by proper compensation. This study recommends that the Ternate City Transportation Service issue technical regulations for collecting parking fees on public roads including determining new parking points and the urgent need for electronification of parking retribution payments in stages as well as adding new parking attendants as well as building cooperation with other parties in the management of parking fees.